LncRNA POU3F3 Contributes to Dacarbazine Resistance of Human Melanoma Through the MiR-650/MGMT Axis - Wu, Kai; Wang, Qiang; Liu, Yu-Lin; Xiang, Zhuo; Wang, Qing-Qing; Yin, Li; Liu, Shun-Li (Frontiers in Oncology, 2021)
Background: Alkylating agents are critical therapeutic options for melanoma, while dacarbazine (DTIC)-based chemotherapy showed poor sensitivity in clinical trials. Long non-coding RNAs (lncRNA) were highlighted in the progression of malignant tumors in recent years, whereas little was known about their involvement in melanoma. Methods: The functional role and molecular mechanism of lncRNA POU3F3 were evaluated on DTIC-resistant melanoma cells. Further studies analyzed its clinical role in the disease progression of melanoma. Results: We observed elevated lncRNA POU3F3 expression in DTIC-resistant melanoma cells. Gain-of-function assays showed that lncRNA POU3F3 overexpression maintained cell survival with DTIC treatment, while lncRNA POU3F3 knockdown restored cell sensitivity to DTIC. A positive correlation of O6-methylguanine-DNA-methyltransferase (MGMT) expression was observed with lncRNA POU3F3 in vitro and in vivo. Bioinformatics analyses predicted that miR-650 was involved in lncRNA POU3F3 regulated MGMT expression. Molecular analysis indicated that lncRNA POU3F3 worked as a competitive endogenous RNA to regulate miR-650 levels. And lncRNA POU3F3/miR-650 axis determined the MGMT transcription in melanoma cells to a great extent. Further clinical studies supported that lncRNA POU3F3 was a risk factor for the disease progression of melanoma. Conclusions: lncRNA POU3F3 up-regulated MGMT expression by sponging miR-650, which was a crucial way for DTIC resistance in melanoma. Our results indicated that lncRNA POU3F3 was a valuable biomarker for the disease progression of melanoma.